Bubble refinement by non-invasive rotating flow. (31st December 2021) - Wang, Lianyu; Liu, Zeyi; Qi, Ji; He, Ming; Sano, Masamichi; Liu, Xiaoming; Zhao, Lijia; Wang, Qiang
Graphical abstract: Highlights: A non-invasive rotating flow for bubble refinement is designed. Bubble size decreases by rotating flow of liquid without using invasive parts. Rotating flow causes the formation size of mother bubble to be small. Turbulent shear stress and turbulent normal stress make mother bubble break into small daughter bubbles. Abstract: Gas–liquid flow widely exists in industrial processes. Bubble refinement is of importance because smaller bubbles lead to higher efficiency of the gas–liquid interaction. Here, the novel rotating flow is designed for bubble refinement without using invasive parts. The drag force along the flow direction and the additional shear-lift force applied on the mother bubble allow it to detach from the orifice more easily with smaller size. In addition, the non-invasive rotating flow generates a large velocity gradient in both the shear and normal directions, resulting in turbulent shear and normal stress, causing the rising mother bubbles to break up in either the shear or normal direction. As a result, the number of bubbles increases to 408 compared to 9 under the static condition. Approximately 50% of the bubbles in the liquid are less than 3.60 mm in size and the Sauter mean bubble diameter is reduced from 10.45 to 4.77 mm, a decrease of 54.41%. The bubble refinement mechanism in the non-invasive rotating flow applies to other occasions where no invasive parts are needed.